Allergic march: a comprehensive approach to diagnosing, treating and preventing atopic diseases - Suwala, Zuzanna; Marchewka, Urszula; Bieńkowski, Borys; Feja, Krzysztof; Łuczak, Ewa; Jachowicz, Krzysztof; Petryla, Piotr; Ostafin, Kamil; Rektor, Natalia; Minkner, Mikołaj (Journal of Education, Health and Sport, 2023)
The article discusses the phenomenon of allergic march, which is a progressive process of atopic disease development in allergic patients. The inflammatory process changes localization, causing various symptoms such as atopic dermatitis, food allergy, asthma, allergic rhinitis and eosinophilic esophagitis. Allergic march has a major impact on the development of asthma and allergic rhinitis. The diversity of allergic march trajectories is due to the interaction of genetic, environmental and psychosocial factors. Understanding these mechanisms is crucial to prevent effectively the progression of allergic diseases. The article also discusses the advantages of sublingual immunotherapy (SILT) in the treatment of allergic diseases. SILT shows safety profile and may be more acceptable treatment option for the patients comparing to the traditional subcutaneous immunotherapy (SCIT). There are evidence of the beneficial effects of SILT in reducing allergy symptoms and improving quality of life in allergic patients.